Electrochemical Cross‐Coupling of C(sp2)−H with Aryldiazonium Salts via a Paired Electrolysis: an Alternative to Visible Light Photoredox‐Based Approach - Jiang, Yang‐ye; Dou, Gui‐yuan; Zhang, Luo‐sha; Xu, Kun; Little, R. Daniel; Zeng, Cheng‐chu (Advanced synthesis & catalysis, 2019)
Photoredox‐based C−H bond functionalization constitutes one of the most powerful and atom‐economical approaches to organic syntheses. During this type of reaction, single electron transfer takes place between the photocatalyst (PC) and redox‐ active substrates. Electrosynthesis also involves electron transfer between substrates and electrodes. In this paper, we focus upon electrochemical cross‐coupling of C(sp2)−H with aryldiazonium salts and have developed an efficient electrochemical approach to the Minisci‐type arylation reaction. The constant current paired electrosynthesis proceeds in a simple undivided cell without external supporting electrolyte, features a wide range of substrates and is easy to scale‐up. These results demonstrate that photoredox‐based cross‐coupling of C(sp2)−H with aryldiazonium salts can also proceed successfully under paired electrolysis conditions, thereby contributing to understanding of the parallels between photosynthesis and electrosynthesis.